Impact of T Status and N Status on Perioperative Outcomes after Thoracoscopic Lobectomy for Lung Cancer - Villamizar, Nestor R. (2012)
OBJECTIVE: We sought to evaluate the effect of tumor size, location, and clinical nodal status on outcomes after thoracoscopic lobectomy for lung cancer. METHODS: All patients who underwent attempted thoracoscopic lobectomy for lung cancer between June 1999 and October 2010 at a single institution were reviewed. A model for morbidity including published risk factors as well as tumor size, location, and clinical N status was developed by multivariable logistic regression. RESULTS: During the study period, 916 thoracoscopic lobectomies met study criteria: 329 for peripheral, clinical N0 tumors ≤3cm and 504 for tumors that were central, clinical node positive, or >3cm; tumor location could not be documented for 83 patients. Conversions to thoracotomy occurred in 36 patients (4%); patients with clinically node positive disease had higher conversion rates [11 conversions in 153 clinical N1-N3 patients (7.2%) vs 25 in 763 clinical N0 patients (3.3%), p=0.03]. Overall operative mortality was 1.6% (14 patients) and morbidity was 32% (296 patients). Although patients with larger tumors (p=0.006) and central tumors (p=0.01) had increased complications by univariate analysis, tumor size >3cm (p=0.17) and central location (p=0.5) did not significantly predict overall morbidity in multivariate analysis. Clinical node status did not predict increased complications by univariate or multivariate analysis. Significant predictors of morbidity in multivariable analysis were increasing age, decreasing FEV1, prior chemotherapy, and congestive heart failure. CONCLUSIONS: Thoracoscopic lobectomy for lung cancers that are central, clinically node positive, or larger than 3 cm does not confer increased morbidity compared to peripheral, clinical N0 cancers that are smaller than 3 cm.